2020
DOI: 10.2176/nmc.oa.2020-0148
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Very Poor Outcome after Mechanical Thrombectomy for Acute Basilar Artery Occlusion

Abstract: Prognosis for patients with acute basilar artery occlusion (BAO) remains poor. Successful revascularization is a main predictor of favorable clinical outcomes after mechanical thrombectomy for BAO. However, even if mechanical thrombectomy is successful, some patients have a poor clinical outcome, including vegetative state and mortality. This study investigated the factors that are predictive of extremely poor clinical outcomes despite successful revascularization after mechanical thrombectomy for BAO. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Li et al 33 found that the maximum length multiplied by thickness in the brainstem may be a predictor for assessing neurologic deterioration. Consistent with our findings, Liu et al 34 and Tajima et al 35 found significantly reduced infarct volumes from the midbrain and pons and that increased caudate volumes had favorable clinical outcomes in patients after EVT. Mourand et al 36 showed that pre-EVT cerebellar infarct volume was an independent predictor of 90-day functional independence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Li et al 33 found that the maximum length multiplied by thickness in the brainstem may be a predictor for assessing neurologic deterioration. Consistent with our findings, Liu et al 34 and Tajima et al 35 found significantly reduced infarct volumes from the midbrain and pons and that increased caudate volumes had favorable clinical outcomes in patients after EVT. Mourand et al 36 showed that pre-EVT cerebellar infarct volume was an independent predictor of 90-day functional independence.…”
Section: Discussionsupporting
confidence: 92%
“…The occipital cortex, thalamus, and cerebellum lesions are less involved in functional outcome than those in the brainstem. 35 The numerous key conduction systems that maintain consciousness and physiologic activities cross the brainstem. 37 This may explain the worse clinical outcome of infarcts in the brainstem region.…”
Section: Discussionmentioning
confidence: 99%
“…19 Baseline NIHSS score is an independent factor for postoperative outcomes, and a lower NIHSS score predicts a better prognosis for patients. 20,21 This study has some limitations. On the one hand, as a single-centre study, the sample size is relatively small.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have demonstrated that several independent factors were associated with in-hospital mortality in patients with anterior circulation large vessel occlusion [4, 5, 8]. However, few studies have established the factors which independently increase the risk of early mortality in BAO, a disorder associated with the highest mortality rate among causes of stroke [19, 20]. The majority of deaths in the first week are due to herniation, hemorrhage, and cerebral infarction according to a previous study [4].…”
Section: Discussionmentioning
confidence: 99%